(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
It is intended to encourage students to pursue independent research and discover the joy of discovery in order to increase students’ interest in natural sciences, particularly in physics, and to encourage them to connect their perceptions of the universe with STEM activities.